Association between uric acid and risk of venous thromboembolism in East Asian populations: a cohort and Mendelian randomization studyResearch in context - Haoyi Weng; Haobo Li; Zhu Zhang; Yu Zhang; Linfeng Xi; Di Zhang; Chao Deng; Dingyi Wang; Ruoyan Chen; Gang Chen; Senwei Tang; Xianbo Zuo; et al. (Elsevier, 2023)
Summary: Background: Serum uric acid (SUA) levels have been associated with an increased risk and recurrence of venous thromboembolism (VTE) in European populations, but the potential causal relationship remains unclear. Large-scale studies on the association between SUA and VTE in East Asian populations are lacking, despite the high prevalence of hyperuricemia in this region. To address this, we conducted a cohort analysis and a two-sample Mendelian randomization (MR) study in East Asian populations. Methods: We collected data on VTE patients from the China Pulmonary Thromboembolism Registry Study (CURES) and compared them to controls obtained from the China Health and Retirement Longitudinal Survey (CHARLS). Propensity score matching (PSM) and cubic-spline models were applied to assess the effect of SUA on VTE risk while adjusting for multiple covariates. We also performed two-sample MR analyses to infer potential causality based on summary statistics from Genome-wide Association Studies (GWAS) of SUA and VTE in the East Asian population. Findings: We found that the SUA levels were higher in VTE patients (317.95 mmol/L) compared to the general population (295.75 mmol/L), and SUA ≥ 325 mmol/L was associated with an increased risk of VTE recurrence (P-value = 0.0001). The univariable MR suggested a causal relationship between elevated SUA and higher VTE risk (Pinverse variance weighted < 0.05), and multivariable MR showed that elevated SUA levels continued to promote the development of VTE after adjusting for multiple covariates (Pmultivariable residual < 0.05). Sensitivity analyses produced similar results for these estimations. Interpretation: Our study provides evidence supporting a robust positive association between SUA and VTE in the East Asian population, and MR analyses suggest that this association is likely to be causal. Our findings underscore the importance of monitoring SUA levels in VTE prevention and call for urgent action to address the growing burden of hyperuricemia in the Asia-Pacific region. Funding: This research was funded by Beijing Nova Program (No. Z211100002121057), National Natural Science Foundation of China (No. 82100065 and No. 62350004), CAMS Innovation Fund for Medical Sciences (No. 2021-I2M-1-061 and No. 2021-1-I2M-001), Elite Medical Professionals project of China-Japan Friendship Hospital (No. ZRJY2021-QM12), National Key Research and Development Project (No. 2021YFF1201200 and No. 2022YFC3341004).